2017
DOI: 10.2176/nmc.oa.2016-0169
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Morbidity and Cleavage Plane in Surgical Resection of Pure Convexity Meningiomas Using Cerebrospinal Fluid Sensitive Image Subtraction Magnetic Resonance Imaging

Abstract: Meningiomas are the most common primary intracranial tumors. Since the adhesions in the plane of dissection are of interest in surgical planning, we suggest that digital image subtraction of FLAIR data from the T2 sequence of MRI may represent better the CSF spaces in the brain–tumor interface and may be a predictor of the intraoperative cleavage plane. From 2006 to 2016, 83 convexity meningiomas were resected in the Department of Neurosurgery of the University Hospital Complex of Vigo, an analysis of preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Considering the results of similar studies, a change in a patient’s mean age at the time of surgery could be observed over the last decades. While the average age a few decades ago was just over 50 years [ 20 , 22 ], meningioma patients who undergo surgery today are approximately 60 years old, similar to this study [ 9 , 21 , 23 , 24 ]. This is not surprising, since the ongoing advances in medicine mean that people are living longer and, consequently, also in the case of patients undergoing surgery.…”
Section: Resultssupporting
confidence: 77%
“…Considering the results of similar studies, a change in a patient’s mean age at the time of surgery could be observed over the last decades. While the average age a few decades ago was just over 50 years [ 20 , 22 ], meningioma patients who undergo surgery today are approximately 60 years old, similar to this study [ 9 , 21 , 23 , 24 ]. This is not surprising, since the ongoing advances in medicine mean that people are living longer and, consequently, also in the case of patients undergoing surgery.…”
Section: Resultssupporting
confidence: 77%
“…Arachnoidal plane constitutes also one prognosticator. Villa et al established the term cleft sign introducing a T2-FLAIR digital subtraction sequence [4]. Edema did not always correlate with the poor cleavage plane.…”
Section: Discussionmentioning
confidence: 99%
“…Edema did not always correlate with the poor cleavage plane. Absent cleft sign in the image subtraction and a minimal intraoperative cleavage plane strongly omens postoperative neurological deficits [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among MR features, tumor shape and brain invasion were significantly different between TM and AM, and based on the stepwise multivariate logistic regression analysis, they can be used as independent discrimination factors. AMs are more irregular, and TMs are mostly circular or quasicircular, which may be related to the grade of the tumor and the increased brain volume due to the peritumoral edema (26).…”
Section: Assessment Of the Clinicoradiomic Nomogram Performancementioning
confidence: 99%